2021
DOI: 10.3389/fpsyg.2020.603632
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Conventional and Technology-Mediated Selection Interviews With Regard to Interviewees’ Performance, Perceptions, Strain, and Anxiety

Abstract: Organizations increasingly use technology-mediated interviews. However, only limited research is available concerning the comparability of different interview media and most of the available studies stem from a time when technology-mediated interviews were less common than in the present time. In an experiment using simulated selection interviews, we compared traditional face-to-face (FTF) interviews with telephone and videoconference interviews to determine whether ratings of interviewees’ performance, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…HRV is conceptualized as one's capacity for emotion regulation and social engagement (Thayer et al, 2009;Thayer & Lane, 2000). Unsurprisingly, HRV has been found to change in the context of a simulated job interview (Melchers et al, 2021;Villada et al, 2017) and higher HRV reactivity (i.e., greatest change from resting to a stressful state) has been found to be related to greater accuracy in perceiving subtle social and emotional cues in a mock interview (Muhtadie et al, 2014). Finally, one study found that interviewees' level of cortisol (hormonal index of physiological arousal) varied depending on their level of social anxiety, such that individuals identified as having high levels of social anxiety (i.e., one feature of the cognitive component of interview anxiety) also exhibited higher levels of cortisol (Budnick et al, 2019).…”
Section: Physiological Componentmentioning
confidence: 99%
See 2 more Smart Citations
“…HRV is conceptualized as one's capacity for emotion regulation and social engagement (Thayer et al, 2009;Thayer & Lane, 2000). Unsurprisingly, HRV has been found to change in the context of a simulated job interview (Melchers et al, 2021;Villada et al, 2017) and higher HRV reactivity (i.e., greatest change from resting to a stressful state) has been found to be related to greater accuracy in perceiving subtle social and emotional cues in a mock interview (Muhtadie et al, 2014). Finally, one study found that interviewees' level of cortisol (hormonal index of physiological arousal) varied depending on their level of social anxiety, such that individuals identified as having high levels of social anxiety (i.e., one feature of the cognitive component of interview anxiety) also exhibited higher levels of cortisol (Budnick et al, 2019).…”
Section: Physiological Componentmentioning
confidence: 99%
“…This preference for face-to-face interviews may result from the fact that in-person interviews facilitate a natural back-and-forth that enables individuals to convey and interpret emotional responses, and provide more opportunities to use nonverbal cues (Chapman & Rowe, 2002;Proost et al, 2020). A more recent study examined anxiety in response to three interview platforms (face-to-face, phone, video-conference) and no significant associations were observed, although the sample consisted of university students in a lab-based study, which calls for additional field-based research (Melchers et al, 2021).…”
Section: Contextual Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason for this non-discrepancy is due to the design differences of different VI platforms, such as the opportunity to fake responses ( Lukacik et al, 2020 ) and restrictiveness in making and correcting errors ( Wong, 2020 ). Another explanation is that experiencing the actual interview lowers the differences between the applicants with prior experience and their counterparts ( Melchers et al, 2021 ). Unlike this study, Wong (2020) found that having no prior VI experiences results in more negative reactions against VI, especially concerning fairness and justice issues, but experiencing VI may help to mitigate pre-interview negative reflections ( Basch et al, 2020a ).…”
Section: Resultsmentioning
confidence: 99%
“…They perceived the VI as inadequate in providing social presence, eye contact, and impression management opportunities. In the same vein, comparing conventional and technology-mediated selection interviews, Melchers et al (2021) concluded that different interview media bring about different performance ratings and perceptions under their inherent attributes.…”
Section: Literature Reviewmentioning
confidence: 99%